Enzymatically hydrolyzed low-density lipoprotein modulates inflammatory responses in endothelial cells - Fenske, Dominic; Dersch, Katrin; Lux, Cornelia; Zipse, Lisa; Suriyaphol, Prapat; Dragneva, Yolantha; Han, Shan-Rui; Bhakdi, Sucharit; Husmann, Matthias (Thrombosis and Haemostasis, 2008)
There is evidence that low-density lipoprotein (LDL) is modified by hydrolytic enzymes,and that the product (E-LDL) induces selective production of interleukin 8 (IL-8) in endothelial cells. Since nuclear factor-kappaB (NF-κB) is a major regulator of IL-8 transcription, we studied its activation in endothelial cells treated with E-LDL. Unexpectedly,the modified lipoprotein not only failed to activate NF-κB, but completely blocked its activation by tumour necrosis factor-alpha (TNF-α) in EA.hy926-cells, as assessed by electrophoretic mobility shift assays and immunofluorescence. Inhibition occurred upstream of NF-κB translocation, as inhibitor of NF-κB- (IκB)-phosphorylation was suppressed by E-LDL. In contrast to NF-κB,transcription factor activator protein-1 (AP-1) proved to be activated. Removal of free fatty acids present in E-LDL obliterated both activation of AP-1 and inhibition of NF-κB. Chromatin immunoprecipitation revealed that phosphorylated c-jun, but not NF-κBp65 bound to the natural IL-8 promoter. Production of endothelial IL-8 and simultaneous modulation of NF-κB in response to hydrolyzed LDL might serve to protect the vessel wall and promote silent removal of the insudated lipoprotein.
Keywords: Enzymatically modified LDL; NF-κB; AP-1; interleukin-8; endothelial cells